2002
DOI: 10.1038/sj.bjc.6600015
|View full text |Cite
|
Sign up to set email alerts
|

Vascular phenotype in angiogenic and non-angiogenic lung non-small cell carcinomas

Abstract: We have previously described a group of non-small cell lung carcinomas without morphological evidence of neo-angiogenesis. In these tumours neoplastic cells fill up the alveoli and the only vessels present appear to belong to the trapped alveolar septa. In the present study we have characterised the phenotype of the vessels present in these non-angiogenic tumours, in normal lung and in angiogenic non-small cell lung carcinomas. The vessels, identified by the expression of CD31, were scored as mature when expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 28 publications
(34 reference statements)
4
84
0
Order By: Relevance
“…The first marker was the expression of the LH39 epitope interacting with the antibody LH39, which is expressed on the basal membrane of capillaries and small venules in a variety of normal human tissues but is absent in small vessels present in pyogenic granulomas or nonspecific oral ulceration (Almeida et al, 1992a, b). These data have suggested that the detection of LH39 staining discriminates between mature and immature vessels, as supported by four further studies on oral carcinomas (Almeida et al, 1992a), breast carcinomas (Kakolyris et al, 1999) and lung cancer (Kakolyris et al, 1999;Passalidou et al, 2002).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…The first marker was the expression of the LH39 epitope interacting with the antibody LH39, which is expressed on the basal membrane of capillaries and small venules in a variety of normal human tissues but is absent in small vessels present in pyogenic granulomas or nonspecific oral ulceration (Almeida et al, 1992a, b). These data have suggested that the detection of LH39 staining discriminates between mature and immature vessels, as supported by four further studies on oral carcinomas (Almeida et al, 1992a), breast carcinomas (Kakolyris et al, 1999) and lung cancer (Kakolyris et al, 1999;Passalidou et al, 2002).…”
mentioning
confidence: 73%
“…Furthermore, the balance between neoangiogenesis and vascular regression, still maintained in neoplastic follicles, is lost in diffuse large cell lymphomas. Large B-cell lymphomas therefore have a vascular (Kakolyris et al, 1999(Kakolyris et al, , 2000Passalidou et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, treated tumors still presented with a nodular phenotype, but the nodules lacked These results suggest that metastatic emboli escape the tumor during early stages of tumor growth. Furthermore, they show that ZD6474 treatment does not inhibit metastatic outgrowth in lungs, possibly reflecting the potential to grow by cooption in highly vascularized tissues (Passalidou et al, 2002;Leenders et al, 2004). Furthermore, the intravascular localization of these metastases, very near to air-filled alveoli, may enable tumor growth without additional angiogenesis.…”
Section: Zd6474 Prevents Formation Of the Metastatic Phenotypementioning
confidence: 99%
“…First, clinical and animal data show that for metastatic tumors in brains, lungs or livers, induction of angiogenesis is not a prerequisite as for these tumors the preexistent vascular bed may allow tumor growth (Pezzella et al, 1997;Al-Mehdi et al, 2000;Neves et al, 2001;Vermeulen et al, 2001;Kim et al, 2002;Kusters et al, 2002;Passalidou et al, 2002;Auguste et al, 2005). Secondly, recent reports demonstrated the presence of intravascular endothelium-covered tumor cell clusters in the primary tumor as origin of metastasis (Sugino et al, 1993(Sugino et al, , 2002(Sugino et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%